Marketing Model for Sintung Islamic Arts as a Halal Tourism Destination Object in Sumenep Regency - R.A. Adisty Nur Fatima Ramadini; Sarkawi .; Lailatul Qadariyah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
This research discusses Islamic arts in Sumenep Regency, one of which is Sintung Arts. This art is a depiction of Madura's Islamic spiritual culture. However, many people in Sumenep, especially young people, do not know about this art, even though it has quite large potential to become a halal tourist destination in Sumenep Regency, as well as a means of da'wah for Muslims. Based on this problem, researchers are interested in researching in more depth how Sintung members introduce this art to the public and trying to formulate or design a marketing model for Sintung Art so that it can be known to the general public, so that this art can continue to develop and be preserved. The method used in this research uses an exploratory qualitative approach. The data used in this research uses primary data and secondary data with data collection techniques through interviews, observation and documentation. The data analysis stage was carried out by means of data reduction, data presentation, and drawing conclusions. Based on the research results, in substance Sintung Art can become a halal tourist destination, both in terms of the art itself, the provision of adequate space, as well as support from the government and the community. Meanwhile, the marketing carried out by Sintung is only limited to spreading traditions to schools in Ambunten. In this way, the marketing model offered through the marketing mix can be an alternative choice for this art so that it can continue to develop and be preserved because this art is unique in its music , vocals and dance movements.